PREPARATION OF METHYL SALICYLATE USE THE ACID CATALYST BY WITHOUT SOLVENTS METHOD - Widyanto Saptawan Priambodo; Daniel Daniel; Chairul Saleh (JURNAL ATOMIK, 2019)
Preparation of methyl salicylate use the acid catalyst by without solvents method has been done. Preparation of methyl salicylate was carried out by reacting salicylic acid with methanol and use sulfonic acid as a catalyst. The raeaction was use reflux method at 60-70 oC for 3 hours. The result of preparation of methyl salicylate were it has a yellow clear solution (like oil) and has a distinctive smell (like gandapura oil). From the result of FT-IR analysis showed the functional groups O-H phenol, C-H sp2, C-H sp3, C=O ester, C=C aromatic, C-O-C ester and C-OH phenol. Based on these results it is known that the methyl salicylate has been formed.